2018
DOI: 10.3329/bjp.v13i2.33313
|View full text |Cite
|
Sign up to set email alerts
|

Antiarthritic efficacy of Clematis orientalis

Abstract: <p class="Abstract"><em>Clematis orientalis</em> has been used traditionally to cure rheumatism, but its efficacy has not been scientifically explored in treating rheumatoid arthritis. The present study was designed to investigate the antiarthritic efficacy of <em>C. orientalis</em> using blockade of heat-induced protein alterations and HRBC membrane stabilization methods along with formaldehyde induced arthritis in rats. Aqueous ethanol (30:70) extract and various fractions (hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The utmost activity was noticed for chloroform extract of root at 500 μ g/ml (63.28 ± 5.96%). The inclusion of flavonoids and phenolic chemicals, which have previously been shown by several researchers, is thought to be responsible for the crude extracts' antiarthritic effect [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The utmost activity was noticed for chloroform extract of root at 500 μ g/ml (63.28 ± 5.96%). The inclusion of flavonoids and phenolic chemicals, which have previously been shown by several researchers, is thought to be responsible for the crude extracts' antiarthritic effect [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC analysis identified different phenolic and flavonoid contents like catechin, ferulic acid, quercetin, gallic acid, caffeic acid and vanilic acid. It was previously reported that the presence of compounds like ferulic acid, quercetin, gallic acid and vanilic acid was responsible for antioxidant and anti-inflammatory potential [ 33 ]. The presence of these compounds in CT extract had also previously been reported [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nature is ever-giving, rich in beneficial natural products, and never depleted (Elisha et al, 2016). Herbal drugs are promising natural alternatives (Hasan and Alamgeer, 2018). Antiarthritic activity of herbal drugs can be tested through the method “protein denaturation assay” using the Sakat et al’s (2010) method.…”
Section: Introductionmentioning
confidence: 99%